The Protective Effects of PSM-04 Against Beta Amyloid-Induced Neurotoxicity in Primary Cortical Neurons and an Animal Model of Alzheimer’s Disease - Park, Hyunjun; Kang, Shinwoo; Nam, Eunjoo; Suh, Yoo-Hun; Chang, Keun-A (Frontiers in Pharmacology, 2019)
Polygala tenuifolia Willdenow is a herb known for its therapeutic effects in insomnia, depression, disorientation, and memory impairment. In Alzheimer’s disease (AD) animal model, there has been no report on the effects of memory and cognitive impairment. PSM-04, an extract from the root of P. tenuifolia Willdenow, was developed with improved bioabsorption. The present study aimed to investigate the neuroprotective effects of PSM-04 on AD and reveal the possible molecular mechanism. The neuroprotective effect of PSM-04 in primary cortical neurons treated with L-glutamate, oligomeric Aβ, or H2O2. PSM-04 exhibited significant neuroprotective effects against neurotoxicity induced by L-glutamate or oligomeric Aβ. Oxidative stress induced by ROS was monitored using the DCF-DA assay, and apoptosis was assessed using the TUNEL assay in primary cortical neurons treated with H2O2 or oligomeric Aβ. PSM-04 also decreased oxidative stress induced by H2O2 and apoptotic cell death induced by oligomeric Aβ. In this study, we evaluated the therapeutic effect of PSM-04 in 5xFAD mice, an animal model for AD. PSM-04 was orally administered to 4-month-old 5xFAD (Tg) mice for two months. To confirm the degree of cognitive impairment, a novel object recognition task was performed. The treatment with PSM-04 significantly alleviated cognitive impairments in Tg mice. In addition, amyloid plaques and gliosis decreased significantly in the brains of PSM-04-administered Tg mice compared with Tg-vehicle mice. Furthermore, the administration of PSM-04 increased the superoxide dismutase-2 (SOD-2) protein level in hippocampal brain tissues. Our results indicated that PSM-04 showed therapeutic effects by alleviating cognitive impairment and decreasing amyloid plaque deposition in Tg mice. Therefore, PSM-04 was considered as a potential pharmacological agent for neuroprotective effects in neurodegenerative diseases, including AD.